Estimating global production and supply costs for green hydrogen and hydrogen-based green energy commodities. (22nd March 2023) - Moritz, Michael; Schönfisch, Max; Schulte, Simon
Abstract: Green energy commodities are expected to be central in decarbonising the global energy system. Such green energy commodities could be hydrogen or other hydrogen-based energy commodities produced from renewable energy sources (RES) such as solar or wind energy. We quantify the production cost and potentials of hydrogen and hydrogen-based energy commodities ammonia, methane, methanol, gasoline, diesel and kerosene in 113 countries. Moreover, we evaluate total supply costs to Germany, considering both pipeline-based and maritime transport. We determine production costs by optimising the investment and operation of commodity production from dedicated RES based on country-level RES potentials and country-specific weighted average costs of capital. Analysing the geographic distribution of production and supply costs, we find that production costs dominate the supply cost composition for liquid or easily liquefiable commodities, while transport costs dominate for gaseous commodities. In the case of Germany, importing green ammonia could be more cost-efficient than domestic production from locally produced or imported hydrogen. Green ammonia could be supplied to Germany from many regions worldwide at below the cost of domestic production, with costs ranging from 624 to 874 /t NH3 and Norway being the cheapest supplier. Ammonia production using imported hydrogen from Spain could be cost-effective if a pan-European hydrogen pipeline grid based on repurposed natural gas pipelines exists. Highlights: Comprehensive database for global production and supply costs with projections until 2050. Production costs are the significant cost component for liquid or easily liquefiable energy commodities. Green hydrogen might be traded regionally via pipeline rather than shipped globally via LH2 . Importing green ammonia is more cost-efficient than importing green hydrogen for domestic ammonia production in Germany. Germany: Only if a low-cost European H2 pipeline grid exists could ammonia production from imported H2 be cost-effective.